A Review of Theories in Gratitude Literature - Subramanian R, Bala; Thakur, Munsih (Psychology Hub, 2022)
Gratitude is not an uncommon emotion that can be easily neglected and deservesempirical and theoretical attention. Gratitude research, initially originated frompsychology, expanded to all fields, in the last two decades. Various theories have beenapplied to explain the gratitude phenomenon in the research. The theories have theirown advantages, and limitations in explaining the gratitude. This paper is a review ofthe theories applied in gratitude research. The paper also analysis the theories in theirscope of level of analysis.